2017
DOI: 10.1016/j.cels.2017.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry between Activation and Deactivation during a Transcriptional Pulse

Abstract: SummaryTranscription in eukaryotic cells occurs in gene-specific bursts or pulses of activity. Recent studies identified a spectrum of transcriptionally active “on-states,” interspersed with periods of inactivity, but these “off-states” and the process of transcriptional deactivation are poorly understood. To examine what occurs during deactivation, we investigate the dynamics of switching between variable rates. We measured live single-cell expression of luciferase reporters from human growth hormone or human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Unfortunately, mechanistically detailed NEQ models entail an explosion in the complexity of the corresponding reaction schemes and the number of associated parameters: On the one hand, such models are intractable to infer from data, while on the other, it is difficult to understand which details are essential for the emergence of regulatory function. As a result, existing models that have been confronted with data typically assume or detect nonequilibrium “state transitions” of a promoter without any reference to TF binding ( 29 32 ) or only include a phenomenological description of how TFs modulate state transition rates ( 33 ). To our knowledge, a class of nonequilibrium gene-expression models that accounts for the chemical kinetics of multiple TF–DNA interactions without losing control over complexity is still lacking.…”
mentioning
confidence: 99%
“…Unfortunately, mechanistically detailed NEQ models entail an explosion in the complexity of the corresponding reaction schemes and the number of associated parameters: On the one hand, such models are intractable to infer from data, while on the other, it is difficult to understand which details are essential for the emergence of regulatory function. As a result, existing models that have been confronted with data typically assume or detect nonequilibrium “state transitions” of a promoter without any reference to TF binding ( 29 32 ) or only include a phenomenological description of how TFs modulate state transition rates ( 33 ). To our knowledge, a class of nonequilibrium gene-expression models that accounts for the chemical kinetics of multiple TF–DNA interactions without losing control over complexity is still lacking.…”
mentioning
confidence: 99%
“…In our earlier work, single-cell imaging of the hPRL WT BAC in pituitary cell lines and tissues showed that the hPRL gene displays dramatic pulses in transcriptional activity ( 19 , 20 ). This activity has been observed for many other genes, including the human growth hormone gene ( 21 ), and appears to be a general phenomenon that is intrinsic to gene regulation ( 21-27 ). The characteristics of these transcriptional pulses may be susceptible to modulation, as part of normal physiological control, and this might be expected to impact on overall levels of gene expression.…”
mentioning
confidence: 78%
“…The asymmetry in timing along with the large difference in the associated transcription rates is responsible for the dynamic appearance of short and intense bursts, and the findings here are consistent with results obtained from fitting switch-type stochastic models to single cell reporter imaging time series data for other genes ( Harper et al ., 2011 ; Hey et al , 2015 ). In particular, Dunham et al (2017 ) further characterize this asymmetry by showing that switches from the OFF to the ON states are typically abrupt and result in short and intense bursts which are followed by a gradual deactivation of the gene. The estimation results for the inverted switch rates ( Fig.…”
Section: Experimental Data Analysismentioning
confidence: 95%